Cymatodera ochlera Barr, a junior synonym of Cymatodera wolcotti Barr, with a comparison to similar species (Coleoptera: Cleridae) - Burke, Alan F.; Zolnerowich, Gregory (Zootaxa, 2014)
Cymatodera ochlera Barr 1972 has been considered to be very similar to but distinct from C. wolcotti Barr 1950. We present evidence to show that these two species are conspecific and C. ochlera should be treated as a junior synonym of C. wolcotti. Cymatodera wolcotti is compared to C. balteata and C. undulata, two species remarkably similar to C. wolcotti. Morphological characters of significant value are presented that confirm C. balteata and C. undulata are separate species. Images of all characters discussed are provided.